Impact of native plant‐parasitic nematode communities on the establishment of Meloidogyne chitwoodi. (27th July 2018) - Garcia, N.; Grenier, E.; Sarniguet, C.; Buisson, A.; Ollivier, F.; Folcher, L.
Abstract : Among plant‐parasitic nematodes (PPNs), the species Meloidogyne chitwoodi constitutes an important agricultural issue and is listed as a quarantine species in the EU. This study investigated whether PPN communities can affect the establishment and expansion of M. chitwoodi during a simulated introduction. An original experimental design was developed on potato in the glasshouse involving four PPN communities derived from a single natural one that was initially grown on different host plants. Meloidogyne chitwoodi was inoculated at two different densities (50 or 1000 second‐stage juveniles (J2) per pot). After 4 months, M. chitwoodi was more abundant in the community showing a low overall abundance of PPNs, decreased in the other PPN communities and failed to establish in five pots out of 80. Results showed that establishment – even starting from a very low inoculum – can occur in all communities even if indigenous PPNs in the community affect the expansion through interspecific competition. The reverse interaction was also observed as PPN taxa were generally less abundant in the 1000 M. chitwoodi J2 inoculation treatments. The proportion of M. chitwoodi males produced was higher in the community showing low overall PPN abundance, suggesting a strong sensitivity of M. chitwoodi to intraspecific competition. The presented results suggest that a low abundance of indigenous PPNs presents a higher risk of expansion of M. chitwoodi even if the introduced inoculum is low.